1968
DOI: 10.1111/j.1432-1033.1968.tb00398.x
|View full text |Cite
|
Sign up to set email alerts
|

Particles of Nuclear Origin Carrying Rapidly Labelled RNA

Abstract: Nuclei of KB cells have been isolated and incubated at 37" in pH 8.0 saline. The experia) Isolated nuclei release well defined nucleoprotein particles, which contain RNAs not deb) These particles carry rapidly labelled RNA. c) In cytoplasm they cosediment with the long known smaller ribosomal particles. d) Chase experiments suggest that nuclear particles are precursors of cytoplasmic particles. ments described in this paper provide evidence that: tectable in untreated nuclei.In higher organisms the bulk of cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1970
1970
1984
1984

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…In general about 35 % of the radioactivity in purified nuclei is released which is in good agreement with previously reported values [31,32]. The progressive aggregation of nuclei provoked by these conditions produces some variation in the final yield of nuclear ribonucleoprotein.…”
Section: Extraction Of Nuclear Ribonucleoprotein From Erythroblustssupporting
confidence: 91%
“…In general about 35 % of the radioactivity in purified nuclei is released which is in good agreement with previously reported values [31,32]. The progressive aggregation of nuclei provoked by these conditions produces some variation in the final yield of nuclear ribonucleoprotein.…”
Section: Extraction Of Nuclear Ribonucleoprotein From Erythroblustssupporting
confidence: 91%
“…This led Olsnes and Pihl to suggest that the function of the informofer protein is to protect the mRNA from non-specific binding to ribosomes. The 2 nuclear mRNP co-sediments on sucrose gradients with the small ribosomal subunit after incubation with KB cell cytoplasm [24] .…”
Section: Function Of the Proteins Of Nuclear Mrnpmentioning
confidence: 99%
“…It is evident that protein molecules would be ideal for such a mechanism in view of their capability to interact with macromolecules like DNA, RNA and the constituents of cell membranes, as well as with small molecular weight effectors inducing allosteric transitions. Samarina et al [5,26] and others [53,54], have shown that nascent mlRNA in the nucleus is already associated with proteins. Much of these ribonucleoprotein complexes, which exist also in HeLa cells [12,55], remain in the nucleus [52, 561.…”
Section: The Visualisation Of Mrna 'Protein Particlesmentioning
confidence: 99%